1997
DOI: 10.1172/jci119642
|View full text |Cite
|
Sign up to set email alerts
|

Taxol-resistant epithelial ovarian tumors are associated with altered expression of specific beta-tubulin isotypes.

Abstract: The treatment of advanced ovarian cancer with taxol is hindered by the development of drug resistance. The cellular target for taxol is the microtubule that is stabilized by the drug. Taxol preferentially binds to the ␤ subunit of tubulin of which there are six distinct isotypes in mammalian cells. We have used highly specific oligonucleotides and polymerase chain reaction to analyze expression of all six ␤ -tubulin genes. Human lung cancer cells (A549) were selected in 12 and 24 nM taxol resulting in cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
488
5
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(521 citation statements)
references
References 55 publications
21
488
5
7
Order By: Relevance
“…For example, β-tubulin mutation and alterations have been shown to be associated with paclitaxel resistance (Ranganathan et al, 1988(Ranganathan et al, , 1996(Ranganathan et al, , 1998Haber et al, 1995;Giannakakou et al, 1997;Kavallaris et al, 1997Kavallaris et al, , 1999. We have shown that α-tubulin also contributes paclitaxel resistance (Han et al, 1999).…”
Section: Bmentioning
confidence: 50%
See 1 more Smart Citation
“…For example, β-tubulin mutation and alterations have been shown to be associated with paclitaxel resistance (Ranganathan et al, 1988(Ranganathan et al, , 1996(Ranganathan et al, , 1998Haber et al, 1995;Giannakakou et al, 1997;Kavallaris et al, 1997Kavallaris et al, , 1999. We have shown that α-tubulin also contributes paclitaxel resistance (Han et al, 1999).…”
Section: Bmentioning
confidence: 50%
“…P-glycoprotein (P-gp), an energy-dependent drug efflux pump shown to confer multidrug resistance (MDR) Pastan, 1988, 1993;Lehnert, 1996;Germann, 1996) 2. alterations in β-tubulin isotypes (Haber et al, 1995;Ranganathan et al, 1988Kavallaris et al, 1997 3. mutations in tubulins (Cabral et al, 1981;Schibler and Cabral, 1986;Giannakakou et al, 1997) 4. up-regulation of caveolin-1 (Yang et al, 1998).…”
mentioning
confidence: 99%
“…These microtubules are also more sensitive to paclitaxel-induced assembly compared to unfractioned tubulin (Lu and Luduena, 1993). Subsequent studies revealed alterations in the expression of specific β tubulin isotypes as result of antimicrotubule drug resistance (Haber et al, 1995;Ranganathan et al, 1996;1998a;1998b;Kavallaris et al, 1997;Kavallaris et al, 1999). In addition, combination studies have shown that cyclosporin A enhances paclitaxel efficacy in lung carcinoma cell lines by modulating β tubulin isotype composition (Ross and Antoniono, 1999).…”
mentioning
confidence: 99%
“…[7][8][9][10] Increased levels of microtubule acetylation and detyrosination have been observed in multiple types of cancer cells, [11][12][13][14][15] and both microtubule-stabilizing and microtubule-destabilizing agents have been widely used in cancer treatment. [16][17][18] However, the clinical applications of these agents have shown the emergence of drug-resistant tumor cells, due to the overexpression of different beta-tubulin isotypes, 19,20 or tubulin mutations. 21 JMJD5 is a member of the JmjC domain-containing protein family, which has been shown to obtain H3K36me2 histone demethylase and hydroxylase activities.…”
Section: Introductionmentioning
confidence: 99%